Enabling Pragmatic Software Testing Education in Brazil through an Education Repository: An Initial Proposal - Gomes, João; Nunes, Kennedy; Rivero, Luis; Viana, Davi; Braz Junior, Geraldo; Almeida, João; Fernandes, Vandecia; Rocha, Simara; Silva, Aristófanes (Proceedings of the Life Improvement in Quality by Ubiquitous Experiences Workshop (LIQUE); 2022: Proceedings of the 2nd Life Improvement in Quality by Ubiquitous Experiences WorkshopDO - 10.5753/lique.2022.19998, 2022)
When teaching software testing, it is essential that the students have access to the practical application of the theoretical concepts regarding software testing techniques. Thus, it is important that support materials and real artifacts are available for the practical application of the testing approaches. Despite this importance, undergraduate students from computer science courses still face difficulties in the practical application of the contents covered in the classroom. In this work in progress, our goal is to support the learning process by offering artifacts that allows students to improve their practical skills in software testing. For this, an analysis of the set of test techniques taught in classes and required by the job market was carried out. We also performed an analysis of the features of the repositories that provide support artifacts for teaching these techniques. Considering that the identified repositories are not in Portuguese, we present a high-fidelity prototype of a new Brazilian repository, aggregating the identified artifacts and proposing new ones for supporting testing teaching.